QUALITY EVALUATION OF RUBBER (Havea brasiliensis) SEED COOKING OIL - Evy Rossi; Dewi Fortuna Ayu; Rudi Muslim (Jurnal Sagu, 2013)
The purpose of this research was to conduct physical optimation of chemical properties of rubber seed oilthat could be used as edible oil. This research was conducted by using the Complete Random Block Designconsists of 4 treatments with 3 replications. The treatments were duration of smoking, respectively 12, 16, 20and 24 hours. The data obtained then be analyzed statistically by using ANOVA. The Results of study showedthat duration of smoking a real effect (P <0.05) on yield and water content of rubber seed oil yield, whereastreatment did not affect significantly (P> 0.05) on acid, iodine, and peroxide values of oil and oil color.Based on the results it can be concluded that the duration of smoking for12 to 24 hours make the quality ofrubber seed oil was that oil not feasible as the cooking oil.Key Words: rubber seed, cooking oil, chemical properties